Implementation of new mechanisms to improve service to taxpayers in the tax administration in Uzbekistan Ways to improve small business (Eurasian Research Bulletin, 2023)
In this article, special attention is paid to further reducing the negative impact on the competitiveness of the republic's economy by gradually reducing the monopoly on commodity and financial markets, improving the efficiency of the system of granting benefits and preferences, as well as reducing the regulatory burden on business entities and radically improving the interaction of taxpayers in the implementation of tax administration and the fulfillment of tax obligations of the republic.